Measurement and Implications of Perfectionism in South Korea and the United States. (April 2019) - Rice, Kenneth G.; Park, Hyun-joo; Hong, Jihee; Lee, Dong-gwi
We evaluated the Short Almost Perfect Scale (SAPS; Rice et al., 2014) in South Korean ( N = 306) and United States ( N = 259) samples. Results supported partial metric invariance for the standards (perfectionistic strivings) and discrepancy (perfectionistic concerns) factors, and for depression and self-esteem. Item responses were unaffected by gender- or age-related bias. Differential item functioning analyses and tests of scalar invariance revealed noninvariance for several items that might reflect culturally relevant issues. There were no differences in SAPS factor means based on invariance tests using the alignment method. For both samples, the standards factor was positively and comparably associated with self-esteem and inversely predicted depression; the discrepancy factor yielded effects in the opposite direction. Results generally supported the use of the SAPS for United States–Korean correlational comparisons. Future work could develop and evaluate additional indicators of perfectionistic concerns for cross-national studies, and increase representation in the samples and breadth of criterion factors.